CARIFTA and the new Caribbean (The Secretariat GeorgetownGY, 1971)
Focuses on CARIFTA and economic integration in the Caribbean. Looks at areas of functional cooperation, some regional institutions and notes further steps in regional integration.
Keywords: CARIFTA